Florida 4-H Camp Counselor Training Guide - Jessica Altum Cooper (EDIS, 2019)
4-H Residential Camp Counselor Training empowers youth ages 14-18 to be positive role models, leaders, and mentors to their campers. This new 38-page guide, written by Jessica Altum Cooper and published by the UF/IFAS Florida 4-H Youth Development program, provides preparation and training modules to help youth reach their full potential as the next generation of community leaders. https://edis.ifas.ufl.edu/4h398